Hindernis oder Brücke? Der Beitrag der Angewandten Linguistik zur Erforschung des Lehrens und Lernens von Fremdsprachen. Obstacle or bridge? The contribution of Applied Linguistics to the study of the teaching and learning of foreign languages - Königs, Frank G. (Glottodidactica, 2016)
There is no doubt that Applied Linguistics has firmly established itself as an independent scientific field. However, there are thematic overlaps in some areas concerning other disciplines. Language Teaching Research is a prime example of how linguistic features can be applied in an instructional context. In a first step, the author investigates both the similarities and differences of Applied Linguistics and Language Teaching Research, before dealing with related topics such as second language acquisition, multilingual didactics, mediation, competences, and sensitivity regarding (foreign) language use. Finally, a response is formulated to the question of whether the field of Applied Linguistics functions as a bridge or an obstacle.